2018
DOI: 10.6061/clinics/2018/e49
|View full text |Cite
|
Sign up to set email alerts
|

Liver biopsy may facilitate pancreatic graft evaluation: Positive association between liver steatosis and pancreatic graft adipose infiltration

Abstract: OBJECTIVES:The number of pancreatic transplants has decreased in recent years. Pancreatic grafts have been underutilized compared to other solid grafts. One cause of discard is the macroscopic appearance of the pancreas, especially the presence of fatty infiltration. The current research is aimed at understanding any graft-related association between fatty tissue infiltration of the pancreas and liver steatosis.METHODS:From August 2013 to August 2014, a prospective cross-sectional clinical study using data fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
0
4
0
1
Order By: Relevance
“…To this end, several studies have attempted to characterize pancreatic steatosis in humans using histopathology 10,11 and in vivo imaging techniques, including magnetic resonance imaging (MRI), [12][13][14][15][16][17][18][19][20] magnetic resonance spectroscopy (MRS), [21][22][23][24] ultrasonography, [25][26][27][28][29][30][31][32][33] computed tomography (CT), [34][35][36] and combinations of these techniques. 37,38 Although MRI and MRS remain the most sensitive imaging options for estimating donor pancreas fat content in vivo, these techniques are time-consuming and impractical to incorporate into the donor workflow.…”
mentioning
confidence: 99%
“…To this end, several studies have attempted to characterize pancreatic steatosis in humans using histopathology 10,11 and in vivo imaging techniques, including magnetic resonance imaging (MRI), [12][13][14][15][16][17][18][19][20] magnetic resonance spectroscopy (MRS), [21][22][23][24] ultrasonography, [25][26][27][28][29][30][31][32][33] computed tomography (CT), [34][35][36] and combinations of these techniques. 37,38 Although MRI and MRS remain the most sensitive imaging options for estimating donor pancreas fat content in vivo, these techniques are time-consuming and impractical to incorporate into the donor workflow.…”
mentioning
confidence: 99%
“…Another study revealed that pancreatic steatosis is common in patients with NAFLD and pancreatic fat content positively correlates with liver steatosis grading determined by histology (Nacif et al, 2018).…”
Section: Hyperechogenic Pancreas Can Be Seen In Both Pancreatic Fibro...mentioning
confidence: 98%
“…Pancreatic steatosis is common in patients with NAFLD, and pancreatic fat content positively correlates with liver steatosis grading determined by histology (46,47) . Patients with histologydetermined liver fibrosis have significantly less pancreatic fat infiltration than those without evidence of liver fibrosis (48) .…”
Section: Correlation Between Non-alcoholic Fatty Liver and Non-alcoho...mentioning
confidence: 99%